Sanitary Enigma: Санитарна енигма - Koteska, Jasna; Kirkova-Naskova, Anastazija (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Jasna Koteska | Јасна Котеска Title (English): Sanitary Enigma Title (Macedonian): Санитарна енигма Translated by (Macedonian to English): Anastazija Kirkova-Naskova | Анастазија Киркова-Наскова Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 107-132 Page Count: 25 Citation (English): Jasna Koteska, “Sanitary Enigma,” translated from the Macedonian by Anastazija Kirkova-Naskova, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 107-132. Citation (Macedonian): Јасна Котеска, „Санитарна енигма“, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): 107-132.